2023
DOI: 10.1001/jamaoto.2023.0824
|View full text |Cite
|
Sign up to set email alerts
|

Association of Hearing Loss With Anatomical and Functional Connectivity in Patients With Mild Cognitive Impairment

Abstract: ImportanceHearing loss is the most important modifiable risk factor for cognitive impairment; however, the association of hearing loss with anatomical and functional connectivity is not fully understood. This association may be elucidated by evaluating the findings of newer imaging technologies.ObjectivesTo evaluate the association of hearing loss with anatomical and functional connectivity in patients with mild cognitive impairment (MCI) by using multimodal imaging technology.Design, Setting, and Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…This study included patients aged between 6.5 and 8 years, who underwent hearing rehabilitation before language development. The IQs identified in the patients after treatment were consistent with previous research looking at the opposite side of the history, deaf people suffer from cognitive deficits in absence of adequate hearing rehabilitation [1][2][3][4].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This study included patients aged between 6.5 and 8 years, who underwent hearing rehabilitation before language development. The IQs identified in the patients after treatment were consistent with previous research looking at the opposite side of the history, deaf people suffer from cognitive deficits in absence of adequate hearing rehabilitation [1][2][3][4].…”
Section: Discussionsupporting
confidence: 87%
“…The absence of differences in terms of cognitive development may indicate that CI works better than HA, as previously shown in the literature [4,6]; in fact, some of the patients in the HA group had moderate hearing loss (Table 3) at T0, which could have impacted the IQs at T1. Indeed, preservation of the auditory functions has been associated with better functioning of all brain connections [2,8,9], and has been shown that severe and moderate hearing loss affects brain development differently [11,20]. Children with mild-to-severe hearing loss tend to develop the right hemisphere of the brain more than healthy subject to compensate the auditory deficit, allowing them to present cognitive abilities like normal hearing subjects [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, the primary observation of Papez circuit involvement is reasonable, as patients with presbycusis are more often accompanied by mood disorders, 41 , 42 cognitive deficits and difficulties in managing social relationships, which is consistent with previous neuroimaging findings. 43 , 44 …”
Section: Discussionmentioning
confidence: 99%